Nullity and termination of the insurance contract according to the rules of Insurance Law No. 07-95 - Boumezber, Badis (Journal of Human Sciences, 2022)
According to the general theory of the contract, the insurance contract is invalidated in the event of failure of one of its pillars (consensual, location, reason), or one of the conditions of its validity such as lack of capacity or corruption of will with one of the defects of consent, and this contract is also voided in the event that one of the parties does not implement the obligation resulting from it. In addition to these cases, there are other reasons for the invalidity and termination of the insurance contract stipulated in Ordinance No. 95-07 related to insurances. Through this research paper, we address cases of invalidity of the insurance contract in (the first requirement), and cases of termination of this contract in (the second requirement).